Improving the food and nutritional security of smallholder farmers in South Africa: Evidence from the InnovAfrica Project - Myeni, L; Moeletsi, M.; Nyagumbo, Isaiah; Modiselle, S.; Mokoena, L.; Kgakatsi, I.B (MDPI, 2021)
This article highlights evidence and lessons learned from the InnovAfrica project conducted by the Agricultural Research Council in collaboration with other international organizations between 2017 and 2021. This project aimed to test and upscale best-bet Sustainable Agricultural Intensification (SAI) practices through Multi-Actor Platforms (MAPs) and improved dissemination strategies across six African countries (viz. Ethiopia, Kenya, Malawi, Rwanda, South Africa and Tanzania). The goal of the project was to improve the food and nutritional security of smallholder farmers in Africa. The article briefly discusses some of the key challenges that smallholder agriculture is facing, results from the agricultural interventions brought in by the InnovAfrica project, evidence-based actions and policy recommendations to improve the sustainable agricultural productivity of smallholder farmers in the South African case study. The study showed that SAI practices increased crop yields and build climate-resilient farming communities. It is recommended that the promotion of SAI practices should be supported by enabling institutions and conducive policies that will enhance access to inputs, market linkages, improved access to credit and good agricultural lands, the establishment of functional farmer groups and participatory learning models. These recommendations can be used by the government and other agencies to develop effective interventions to improve food and nutrition security.